Penerapan Fuzzy Inference System Metode Mamdani Untuk Penentuan Besaran Persentase Beasiswa Mahasiswa Baru Universitas Tanri Abeng - Wina Apriliani; Andi Abi Dzar; Rosita Rosita; Nur Afny C. Andryani (Jurnal SISKOM-KB (Sistem Komputer dan Kecerdasan Buatan), 2018)
Scholarship awards consideration involve various parameters. It is set up to make sure the appropriate scholarship assignment. To provide automatic system which is able to assign the scholarship based on given requirements, fuzzy based application is proposed. The Mamdani Fuzzy Inference System is applied to do logic inference to support decision making on scholarship award. To develop the intended application, there are four stages on the research methodology that have been done. They are fuzzification process, rules development, inference rules implementation, and defuzzification process. Meanwhile, Observation, Interview and documentation with The Tanri Abeng University related officers had been done to collect the required data. The proposed application is able to assist the scholarship awards decision maker by providing more efficient and objective measurement.